School Family Partnership Management in Character Development of Students in Secondary Education - Noneng Sri Rahayu; Lilis Suwandari (At Turots: Jurnal Pendidikan Islam, 2026)
Schools as educational institutions have the responsibility to provide an environment that supports the development of student character. In this case, the management of school partnerships with students becomes an important aspect to ensure that positive values can be conveyed and well received by students. The purpose of this study was to obtain information/description and analyze the Management of School Partnerships with Families in the Development of Student Character at SMA Negeri 1 Kawali and SMK Negeri 1 Kawali, Ciamis Regency. This study used a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation studies. The results of the study indicate that partnerships that are well managed through intensive communication, involvement of parents and families in school activities, and understanding of the vision of character education between schools and families, can have a positive impact on the behavior and character values of students. The main supporting factors are the leadership of the principal, the openness of teachers, and the active participation of parents. As a suggestion, schools need to develop a structured and sustainable partnership program, carry out targeted communications as well as conduct training for teachers and parents to strengthen synergy in fostering student character. This research is recommended for teachers as a liaison tool to improve collaboration with families. It also serves as a platform for schools to create synergy in supporting student character development. It also serves as a platform for supervisors to encourage schools to build active partnerships with families to support student character development. It also serves as a resource for future researchers to develop more effective partnership models within the context of character education.